Características quantitativas da carcaça de cordeiros Santa Inês, abatidos com diferentes espessuras de gordura subcutânea - Queiroz, Larissa De Oliveira (2015)
AbstractThe present work aimed to study the carcass quantitative characteristics of Santa Inês lambs in a feedlot, slaughtered of three different subcutaneous fat thickness (SFT) levels. Were used for a total of 24 uncastrated lambs with 100 days of age and 22.7 ± 3.75kg body weight. The animals were randomly distributed into one of the three groups: slaughtered at 2, 3 and 4mm of subcutaneous fat thickness (SFT) levels, with eight lambs of each SFT. The data analyses was done by SAEG software using Tukey test at 5% significance level. The lambs slaughtered at 2 mm of SFT showed higher yields of liver (2.12%), spleen (0.32%), head (6.69%) and legs (3.08%), however, for higher values of SFT the yields decreased. The carcass source yield, carcass slaughter yield, carcass commercial yield, carcass biological yield, the body weights and carcass weights were influenced by SFT (p<0.05), the lambs slaughtered at 4 mm SFT showed higher values than the lambs slaughtered at 2 mm SFT. When the level SFT was increased of Longissimus dorsiwere found that increased fat proportion, decreased bone proportion and no have effect of muscle proportion. In conclusion, we recommend to slaughter lambs at 3 mm subcutaneous fat thickness level, because this provided better results for carcass quantitative characteristics.